Seasonal Storage of Distant Industrial Excess Heat for District Heating - Friberg, Ida (My University, 2015)
Large parts of district heating used in Gothenburg originates from excess heat generated from industries near the city. There is potential to utilise more excess heat in Gothenburg from distant industries. This will however require a connecting pipeline of considerable length with high investment cost. This thesis investigates whether the economical benefits of such a pipeline can be increased by installing an additional borehole thermal energy storage (BTES) and an electricity driven heat pump. Investigations have been made for two locations, western Gothenburg and Kung alv. The behaviour of the BTES has been analysed with the Duct Storage Model using the software PILESIM 2. The district heating system has been simulated with the software Martes. Simulation data including prices of fuels, taxes and political instruments used for this study are based on the forecasts of the local district heating company, G oteborg Energi AB. The investment cost of the BTES is based on previously performed master thesis project at Göteborg Energi AB. The results indicate that the potential to make profits from the proposed BTES and the heat pump system under the prescribed project restrictions is rather poor, especially for Kungälv. Western Gothenburg qualifies as an better location from an economical point of view. The COP of the heat pump and electricity price have large impact on the economical results. The choice of interest rate also has a large in uence on the economical feasibility of the project.
Keywords: Samhällsbyggnadsteknik; Energi; Hållbar utveckling; Civil Engineering; Energy; Sustainable Development